Improving the efficiency of extinguishing forest grass-roots fires with knapsack forest fire extinguishers - Zhuravleva Larisa (E3S Web of Conferences, 2023)
The most effective means of fighting forest fires is the timely detection of fires, monitoring and patrolling of recreation areas, extinguishing of unquenched fires. The purpose of the research is to increase the efficiency of extinguishing forest grass-roots fires with knapsack forest fire extinguishers based on constructive and technical solutions that ensure economical use of fire extinguishing agents. The article presents studies of the characteristics of sprayed water, water vapor, affecting the effectiveness of extinguishing. Optimal ratios of the design parameters of the developed knapsack forest fire extinguishers are given. With a short-term exposure to steam on the hearth, diffusion combustion stops. The condition for stopping the burning of wood is the cessation of flame combustion and cooling of coals formed during combustion to a temperature below the pyrolysis temperature, i.e. below 200 ° C. In the case of heterogeneous combustion, the effect of a jet of water vapor on the centers of smoldering is ineffective. To cool the diffusion flame torch, a steam consumption of 1.9 kg per kilogram of wood is required. The water vapor consumption required to dilute the gaseous pyrolysis products formed from one kilogram of wood is about 7 kg. The presented experimental studies confirm the effectiveness of sprayed water and steam as independent extinguishing agents and means of creating support strips. To achieve a critical level of moisture content, the thickness of the condensate film should be at least 0.1 mm. The effective velocity of the steam source is about 1.5-2.5 km/h.